A validated LC–MS/MS method for fast detection of thiodiglycolic acid in aqueous samples. Issue 5 (8th April 2016) - Rodin, Igor; Braun, Arcady; Stavrianidi, Andrey; Baygildiev, Timur; Rybalchenko, Igor; Shpigun, Oleg
ABSTRACT: A novel sensitive screening method based on liquid chromatography–tandem mass spectrometry (LC–MS/MS) has shown the feasibility of separation and detection of thiodiglycolic acid in aqueous samples. The analysis of this compound is of interest since it is specific microbiological metabolite of thiodiglycol, which is precursor and degradation product of chemical warfare agent sulfur mustard. The LC–electrospray ionisation (ESI)–MS method provides a sensitive and direct approach for thiodiglycolic acid identification and quantification using non-extracted non-derivitised samples from aqueous solutions. Chromatographic separation of the thiodiglycolic acid was produced using a reverse phase LC column with gradient mobile phases consisting of 0.1% formic acid in water and acetonitrile. Identification and quantification of species were achieved using ESI–tandem MS monitoring two precursor-to-product ion transitions for thiodiglycolic acid. The method demonstrates linearity over at least two orders of magnitude and detection limit of 10 ng...mL – 1 in environmental water samples.